The THE CHANGE OF CUSTOMER VALUE AS THE IMPACT OF THE DEVELOPMENT OF MARKET ORIENTATION AND RESOURCES CAPABILITY IN SMALL AGRO BUSINESS: EMPIRICAL STUDY IN EAST JAVA - Bagus Nurcahyo,; Ditiya Himawati,; Lince Afriyenny, (Advances in Social Sciences Research Journal, 2020)
Small agro business is one type of creative business that can be used as a processed product and is currently being developed by the local municipal government. In general, the national agro commodity has increased but the small agro business are still limited and not widely known by the wider community so that the right strategy is needed in marketing thier product. This research is motivated by the decline in customer trust which can later influence customer value in small agro businesses. The purpose of this study was to analyze the effect of market orientation and resource capabilities both partially and simultaneously on customer value and to find out the variables that most influence on customer value in small agro businesses in East Java, represented by two cities, namely Blitar and Bojonegoro. This research is descriptive and verificative using explanatory survey, which explains the effect of the independent variable on the dependent variable. The type of data used is primary data and secondary data. The census method is used for the selection of respondent data. Data collection was carried out by means of observation, interviews, and the distribution of questionnaires to 115 respondents of small agro business operators in East Java, represented by Blitar and Bojonegoro. Technical analysis of the data is done by normality test, t test, F test, and determination test. The results of the study indicate that market orientation partially influence customer value and resource capability does not affect customer value in small agro businesses in East Java. While simultaneously market orientation and resource capabilities affect customer value in small agro businesses in East Java. Market orientation is the most influential variable on customer value because it has a significance value of 0,000 while resource capability does not affect customer value because it has a significant value of 0.092 exceeding the ideal criteria of 0.05. The better market orientation can create good customer value because it is focused on the customer, be careful in facing competition and establish good coordination between functions.